Analisis Komponen Pajak Atas Transaksi Penjualan Bahan Bakar Minyak Pada SPBU Shell Tahun 2016 (Studi Kasus PD. Trimitra Utama) - Budhi Yuwono (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
The research is aimed to analyze the extent to which the component of Tax on Oil Fuel Sale Transaction at Shell Gas Station Year 2016. The research method used in this research is qualitative method through in-depth interviews to the informants as many as 3 people with various qualifications and knowledge in their respective fields especially taxation.Based on the analysis show that: the income tax payment obligations have been implemented and reported by PD PT Tri partner.Based on the analysis shows that: The obligation of payment of Income Tax has been paid and reported by PD. PT Tri Mitra Utama.The findings indicate that in the sales, not only fuel sales, but there are other sales such as lubricants and others where the tax is in accordance with the tax regulations, but there are still grey area, that is the existence of margin / operating profit derived from sales of fuel, where the assumption of the taxpayer (PD PT Tri Mitra Utama)that because the tax object has been subject to final tax, but there is no legislation or regulationn on the treatment of the operating profit.